Information Layers of Ostentive Communication of Hoaxes in the Perspective of Relevance Theory of Sperber & Wilson - Rahardi, R. Kunjana; Budhiono, R. Hery (Balai Bahasa Kalimantan Tengah, 2024)
This study aims to find informational layers in the ostentive communication of fake news and to find the types of intent in ostentive communication. The objects of this study are layers of information and intuitive intents in ostentive communication. The data of this study are in the form of excerpts of speech containing layers of information and types of intent in ostentive communication. The source of substantive data for this study is fake news as a manifestation of social texts that are present on social media. Data were obtained by applying the listening method, especially listening which is free of conversation, supported by the understanding of reading and note-taking techniques. The data that has been collected is then classified and typed to facilitate analysis. The analysis was carried out by applying the matching method, especially extralingual matching. The matching method in this study cannot be separated from the context. The steps in data analysis are (1) identifying, (2) reducing, (3) interpreting, and (4) drawing conclusions. This study produces research findings on layers of information and types of intuitive intent in ostentive communication as follows (1) informational layer with intuitive intent to provoke, (2) to worsen the atmosphere, (3) to defame, (4) to insult someone, and (5) informational layer with intuitive intent to incite.